The Effects of Parent-Adolescent Communication on Pathological Internet Use - Aliza, Novia Fetri (Al-Qalb : Jurnal Psikologi Islam, 2022)
Abstract: Adolescence is a transitional period filled with pressure and stress, a turbulent period filled with conflict and mood swings where the role of the family for adolescents is very important in shaping their personality so that they will not commit deviant acts. This study is aimed at knowing the effect of parent-adolescent communication on pathological internet use. The research employed quantitative method using simple regression analysis. The research subjects were the students of Universitas Muhammadiyah Yogyakarta aged 18-21 years. The results of this study based on the coefficient table show a significant value of 0.000 <0.05 which means that there is an effect of variable X (parent-adolescent communication) on variable Y (pathological internet use). For the coefficient of determination value (R Square), it is 58.5%. Meanwhile, the most significant aspect of communication on pathological internet use is communication is a fun thing amounted to 54.8%. It is concluded that parent-adolescent communication has an effect on pathological internet use of the adolescents at Universitas Muhammadiyah Yogyakarta.Â